Identification and detection of virulence genes among Pseudomonasspp isolated from Wayanad - R. G. Sacharia; K. C. Bipin; P. M. Deepa; R. L. Rathish; C. Ravishankar (Journal of Veterinary and Animal Sciences, 2022)
A study was conducted to identify virulence genes of Pseudomonas spp. from 20 cases of canine otitis externa in Wayanad district of Kerala. The samples were collected aseptically and bacterial isolates were identified using culture and biochemistry. The nine identified Pseudomonas isolates were selected and further confirmed by PCR, targeting Opr I gene at genus level. Presence of virulence genes viz. Las A, Las B, Lec A, Lec B and Apr were examined in the confirmed isolates. All the samples were positive for Las B and Apr. Five among the isolates were having Lec A gene. None of the isolates possessed Lec B and Las A gene. Presence of Las B and Apr gene indicate biofilm forming ability of the isolated Pseudomonas organisms.